2019
DOI: 10.31557/apjcp.2019.20.2.639
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytotoxicity Activities of Karamunting (Melastoma malabathricum L.) Fruit Ethanolic Extract and Quercetin

Abstract: Melastoma malabathricum L. is a type of plant naturally grows in Kalimantan that has medicinal properties. Ethanolic extract of M. malabathricum L. flower has quercetin and kaempferol contents that have antioxidant and anticancer activities. But the antioxidant and cytotoxicity activities of M. malabathricum L. fruit ethanolic extract were not known. This study measured the quercetin and kaempferol level in M. malabathricum L. fruit ethanolic extract using HPLC MS/MS, antioxidant activity using DPPH method, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Moreover, the response to particular chemical would up to the dose apply. It was reported quercetin glycosides, which is also abundant in our F1, exhibit the antioxidation or ctotoxicity at low or high IC50, respectively [19]. Hence the dose of AE was determined and treated appropriately to attenuate the apoptosis marker in the present in vitro model (Fig 2).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the response to particular chemical would up to the dose apply. It was reported quercetin glycosides, which is also abundant in our F1, exhibit the antioxidation or ctotoxicity at low or high IC50, respectively [19]. Hence the dose of AE was determined and treated appropriately to attenuate the apoptosis marker in the present in vitro model (Fig 2).…”
Section: Discussionmentioning
confidence: 95%
“…They also compared the extract to quercetin in terms of antioxidant and cytotoxic properties. The authors concluded that the extract exhibits antioxidant (IC 50 : 16.82 ± 0.24 ppm) and cytotoxic properties (LC 50 : 313.44 ppm) which may be attributed to the presence of quercetin [69]. The compounds such as flavonoids, naringenin, and kaempferol-3-O-(2′′,6′′-di-Op-trans-coumaroyl)glucoside, isolated from the flower of M. malabathricum, have been proved to be the potent inhibitor of MCF7 with IC 50 values of 0.28 μM and 1.3 μM [70].…”
Section: Cytotoxic Activity Of Melastomaceaementioning
confidence: 99%
“…Fruits provide vitamins and minerals for daily diet and are a major source of phytoestrogens, anti-inflammatory agents, and antioxidants [17]. One type of herb whose fruit contains antioxidants is Melastoma malabatchricum fruit (M. malabathricum Merr) [18]; [19]. M. malabatchricum (M. mabathricum Merr) is a quite abundant shrub in Central Kalimantan.…”
Section: Introductionmentioning
confidence: 99%
“…Several research results state that certain parts of the M. malabatchricum plant have several benefits, including leaf extract as an antifungal and anti-microbial [21]. Other studies have revealed some of the benefits of M. malabatchricum fruit as a natural textile dye, natural food coloring, and antioxidant effects [18]; [19].…”
Section: Introductionmentioning
confidence: 99%